Optimization and molecular identification of PUA-14 bacterial isolate from protease-producing mangrove waters - Yorasakhi Ananta; Feskaharny Alamsjah; Anthoni Agustien (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Ananta Y, Alamsjah F, Agustien A. 2025. Optimization and molecular identification of PUA-14 bacterial isolate from protease-producing mangrove waters. Biodiversitas 26: 190-198. Protease enzymes, the hydrolase enzymes that break down proteins into simpler molecules, are a vital component of the food, pharmaceutical, and other chemical industries. By selecting microorganisms as enzyme producers, we can meet the high demand for enzymes and promote sustainable production. This study aimed to determine the optimum conditions for protease production by protease-producing PUA-14 bacterial isolates from mangrove waters and to identify the isolates through biomolecular analysis. We conducted laboratory experiments to optimize protease production by varying carbon sources, nitrogen sources, trace elements, and inoculum concentrations. The optimization process employed the One Factor at A Time (OFAT) approach and the Central Composite Design (CCD) within the framework of Response Surface Methodology (RSM) using Design Expert 13 software. Furthermore, biomolecular analyses, including DNA isolation, amplification, and sequencing, were performed to identify the bacterial isolates. The study identified the optimum conditions for protease production by the PUA-14 bacterial isolate are 0.5% lactose, 2.5% NaNO3, Zn as the trace element, and 2.5% inoculum concentration. Molecular analysis confirms the similarity of the PUA-14 bacterial isolate to Bacillus pseudomycoides strain LB-AsDX1-3. These research findings not only provide a foundation for future research but also have immediate practical implications, highlight the potential for sustainable enzyme production under optimized conditions, and support a wide range of industrial applications.